THE CONSITUTIONAL OBLIGATION OF AN IDENTICAL TAX TREATMENT OF MARRIAGE, COMMON LAW PARTNERSHIPS AND SAME-SEX PARTNERSHIPS IN THE REPUBLIC OF SERBIA - Kostić, Svetislav V. (Pravni zapisi, 2022)
In this paper the author focuses on the question of the tax treatment of same-sex partnerships in comparison to the treatment provided for heterosexual marriages and common law partnerships (extramarital unions) in the Serbian law. Namely, different treatment of certain social phenomena can represent a prohibited form of discrimination only under the condition that we show that the observed phenomena are comparable, precisely from the view point of the object of protection provided by the prohibition of discrimination. The problem we face is that our understanding of certain phenomena has changed over time, as best illustrated by the fact that Aristotle, who introduced the concept of discrimination, would have found it difficult to understand the postulate that all people are equal in their rights and obligations before the law. The author starts from the premise that the tax treatment of same-sex partnerships should be viewed through the perspective of the principle of equality in tax law, the principle contained in Article 91, para. 2 of the Serbian Constitution, which stipulates that the obligation to pay taxes and other duties shall be general and based on the economic power of taxpayers. Therefore, if a same-sex union contains the same aspects that affect the economic power of taxpayers, aspects that exist in the case of heterosexual marriage and extramarital union, then the Serbian Constitution requires us to provide it with equal tax treatment resulting from living in a heterosexual partnership. In this way the author opens up the space for a critical review of the tax norms in the 2021 Draft Law on Same-Sex Partnerships, i.e. for proposing solutions that would enable easier, and above all more sustainable key goal the law aspires to, which is to eliminate discrimination of the same-sex partnerships in the Serbian legal system.